Оценка качества систем автоматизированного контроля и слежения за нераспространением радиационных материалов - Забулонов, Ю.Л.; Коростиль, Ю.М.; Буртняк, В.М. (Моделювання та інформаційні технології, 2010)
The article analyzes the ways to assess the quality of automated control and monitoring of non-proliferation of radioactive materials in the light of the fact that for the designers assessment of this quality is already important at the stage of designing a system in order to forecast the demand for the product as well as the expected costs of its development and maintenance.